2020
DOI: 10.1016/s1470-2045(19)30690-4
|View full text |Cite|
|
Sign up to set email alerts
|

Entrectinib in ROS1 fusion-positive non-small-cell lung cancer: integrated analysis of three phase 1–2 trials

Abstract: Implications of all the available evidence Entrectinib is an important therapeutic option for patients with ROS1 TKI-naïve ROS1 fusion-positive NSCLC. The intracranial activity of entrectinib is of particular importance, given the frequency of CNS involvement in ROS1 fusion-positive NSCLC and the limited ability of crizotinib to penetrate the CNS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
286
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 374 publications
(290 citation statements)
references
References 28 publications
1
286
0
3
Order By: Relevance
“…In addition to crizotinib, other TKIs have shown clinically meaningful and durable responses in ROS1rearranged NSCLC patients, including ceritinib, lorlatinib, and entrectinib, which have been shown to have better intracranial effects compared to crizotinib [23,24]. In particular, entrectinib, an orally administered selective inhibitor of ROS1/NTRK/ALK, was demonstrated to be more potent compared to crizotinib and was designed to penetrate the blood-brain barrier, which is of vital clinical importance as the central nervous system (CNS) is the first and sole site of progression in almost half of patients with ROS1 fusion-positive NSCLC who are treated with crizotinib [25,26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to crizotinib, other TKIs have shown clinically meaningful and durable responses in ROS1rearranged NSCLC patients, including ceritinib, lorlatinib, and entrectinib, which have been shown to have better intracranial effects compared to crizotinib [23,24]. In particular, entrectinib, an orally administered selective inhibitor of ROS1/NTRK/ALK, was demonstrated to be more potent compared to crizotinib and was designed to penetrate the blood-brain barrier, which is of vital clinical importance as the central nervous system (CNS) is the first and sole site of progression in almost half of patients with ROS1 fusion-positive NSCLC who are treated with crizotinib [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, entrectinib, an orally administered selective inhibitor of ROS1/NTRK/ALK, was demonstrated to be more potent compared to crizotinib and was designed to penetrate the blood-brain barrier, which is of vital clinical importance as the central nervous system (CNS) is the first and sole site of progression in almost half of patients with ROS1 fusion-positive NSCLC who are treated with crizotinib [25,26]. Drilon et al [23] reported an ORR of 77% in a cohort of ROS1-rearranged NSCLC patients undergoing frontline treatment of entrectinib, demonstrating both favorable systemic and intracranial activities. Collectively, these findings have broadened the therapeutic options for ROS1-positive patients, regardless of CNS metastases at baseline.…”
Section: Discussionmentioning
confidence: 99%
“…Receptor tyrosine kinase fusions are actionable driver alterations in solid malignancies (1). Tyrosine kinase inhibitors (TKIs) targeting these fusions such as crizotinib and entrectinib for ROS1 fusionpositive non-small cell lung cancer (NSCLC) and larotrectinib and entrectinib for TRK fusion-positive malignancies have been approved for clinical use (2)(3)(4)(5). Resistance to these TKIs invariably develops and usually involves second site mutations such as gatekeeper mutation, xDFG motif mutations, and solvent-front mutation (1).…”
Section: Introductionmentioning
confidence: 99%
“…Entrectinib is already marketed in the USA where on 15 August 2019 FDA has issued an accelerated, tissue-agnostic approval to the drug to target solid tumour types bearing NTRK fusions and for the treatment of metastatic ROS1 fusion-positive NSCLC and in Japan where it was approved in June 2019 for the treatment of patients with NTRK fusionpositive tumours and in February 2020 for the treatment of patients with ROS1 fusionpositive NSCLC. [4][5][6][7] The registration of entrectinib for NTRK fusion-positive tumours represents the pharmaceutical conclusion of a scientific history lasting for more than three decades (figure 1). In 1983 Mariano Barbacid, working in the lab of Stuart Aaronson, identified in a colorectal cancer specimen an inversion within chromosome 1 resulting in a fusion oncogene that was named TRK (tropomyosin receptor kinase).…”
Section: The Past Of Entrectinibmentioning
confidence: 99%
“…The substantial intracranial activity of entrectinib confirmed in the clinical settings is particularly relevant for the treatment of patients with ROS1-positive NSCLC because of the high frequency of brain metastases at the diagnosis in this population and the suboptimal ability of crizotinib to penetrate the brain. 6…”
Section: The Past Of Entrectinibmentioning
confidence: 99%